INCREASING THE CREATIVITY OF CHILDREN AGED 4-6 YEARS THROUGH PICTURE STORIES IN THE NUR SUCI PLAY GROUP PANGKEP REGENCY - A.Suci Rahmadani; Nasaruddin; Supriadi (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The formulation of the problem in this research, can picture stories increase the creativity of students at the age of 4-6 years? This study used the Classroom Action Research method with a success indicator of 85% of the 20 students. The results of the research on student creativity experienced an increase in the first cycle of students who developed very well (BSB) totaling 5 students with a percentage of 25%, while in cycle II it increased to 17 students with a percentage of 85% indicating that the application of picture stories can increase creativity child. This is evident from the results of research which showed an increase in children's creativity with indicators of creative thinking, creative attitude, and creative work during the first cycle of research and the results of cycle II were 85%.